Content-based instruction in the flipped classroom to enhance EFL learners’ intercultural communicative competence - Husniah, Rohmy; Lischynsky, Nicholas; Abu, Abdul Ghani; Natchiar, Farah (Universitas Muhammadiyah Gresik, 2020)
The use of educational technology has given rise to the flipped classroom in providing learners with opportunities for active learning and engaging with material inside and outside class. Many previous studies have reported students’ satisfaction in using the flipped classroom for medical, math, and English courses; however, research on using flipped classroom to enhance learners’ intercultural communicative competence (ICC) in the EFL classroom remains insufficient. Therefore, this paper studies a one-semester project in which learners developed their ICC skills through content-based instruction (CBI) in a flipped classroom setting. Twenty-six students in the English department of a private university in Indonesia participated in this study. Using qualitative data analysis, the results show that CBI and flipped classroom improved the participants’ ICC significantly. These results could be valuable for those who wish to conduct similar research.